Antioxidant and Antidiabetic Effects of Flemingia macrophylla Leaf Extract and Fractions : In vitro, Molecular Docking, Dynamic Simulation, Pharmacokinetics, and Biological Activity Studies - Kaniz, Fatema; Ayesha Akter, Sharmin; Jinat Fatema, Sharna; Md. Anamul, Haque; Mst. Mahfuza, Rahman; Shahin, Sarker; Mohsin, Kazi; Md. Rezaur, Rahman; Murtala, Namakka; Monir, Uzzaman; Md Abdul Majed, Patwary (North Carolina State University, 2024)
Flemingia macrophylla has traditionally been applied to relieve inflammation, diabetes, and circulatory complications. The leaf extract of F. macrophylla and its fractions were investigated for their in-vitro antioxidant and anti-diabetic properties. The phytochemical screening showed valuable phytochemicals, including glycosides, flavonoids, saponins, etc. GC‒MS analysis of the phytochemicals in the methanol extract detected 19 bioactive compounds. Among the diverse fractions, the ethyl acetate fraction (EFM) exhibited the highest phenol and flavonoid contents of 557 mg GAE/g and 326 mg QCE/g, respectively. The total antioxidant content of EFM was found to be 292.41±19.16 mg AAE/g, while its antidiabetic study showed the greatest level of α -glucosidase (IC50: 11.27±1.25 µg/mL) and α -amylase (IC50: 10.04±0.63 µg/mL) inhibitory effects. The docking results showed that C6 had the highest binding scores of -9.0, -7.4, and -7.6 kcal/mol against antioxidant (6NGJ), α-glucosidase (5NN5), and α-amylase (4GQR) proteins, respectively. The dynamics simulation disclosed that C6-receptor protein complexes remained stable at the binding pocket under human body conditions and retained their stiff morphology for 100 nanoseconds (ns). ADMET results demonstrated their noncarcinogenic and well-absorbed properties, where PASS prediction data confirmed their efficacy as an antioxidant, antiulcerative, thrombolytic, and antidiabetic. Therefore, F. macrophylla has potential health benefits.